2019
DOI: 10.1002/jpen.1521
|View full text |Cite
|
Sign up to set email alerts
|

PEP uP (Enhanced Protein‐Energy Provision via the Enteral Route Feeding Protocol) in Surgical Patients—A Multicenter Pilot Randomized Controlled Trial

Abstract: Background The Enhanced Protein‐Energy Provision via the Enteral Route Feeding Protocol (PEP uP) has been shown to be feasible, safe, and effective in delivering significantly more energy/protein, though it has not been well studied in surgical/trauma patients. We hypothesized that PEP uP will effectively increase energy/protein delivery to critically ill surgical/trauma patients. Methods This multicenter, prospective, randomized pilot study included adult patients admitted to surgical service who were expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…PEP uP patients received more protein (106.8 ± 37.0 vs 78.5 ± 30.3 g/d; p ¼ 0.02), whereas energy delivery was not significantly different (1400.0 ± 409.5 vs 1237.9 ± 459.1 kcal; p ¼ 0.25). Vomiting was more common in PEP uP patients (32% vs 12%; p ¼ 0.03) and authors cited that although the protocol was effective in increasing protein intakes, it was difficult to implement [107]. The results of this study suggest achieving high-protein intake via EN alone may be difficult in clinical practice.…”
Section: Enteral Nutritionmentioning
confidence: 76%
See 1 more Smart Citation
“…PEP uP patients received more protein (106.8 ± 37.0 vs 78.5 ± 30.3 g/d; p ¼ 0.02), whereas energy delivery was not significantly different (1400.0 ± 409.5 vs 1237.9 ± 459.1 kcal; p ¼ 0.25). Vomiting was more common in PEP uP patients (32% vs 12%; p ¼ 0.03) and authors cited that although the protocol was effective in increasing protein intakes, it was difficult to implement [107]. The results of this study suggest achieving high-protein intake via EN alone may be difficult in clinical practice.…”
Section: Enteral Nutritionmentioning
confidence: 76%
“…The multicentre, prospective, randomized pilot study (PEP uP; N ¼ 36) assessed the PEP uP protocol, which included initiation at goal rate, semi-elemental formula, prophylactic prokinetic agents, 24-h volume-based goals, and modular protein supplementation [107]. Slow recruitment resulted in early trial termination by the sponsor.…”
Section: Enteral Nutritionmentioning
confidence: 99%
“…However, previous observational studies including worldwide surveys [6,7] showed that nutrition targets, especially for protein, were often never achieved and with a number of barriers limiting adequate nutrition therapy [8,9]. Some approaches related to ICU administrative structures, such as dietitian participation [10] or nutrition protocols [11], may contribute to achieving nutrition targets.…”
Section: Introductionmentioning
confidence: 99%
“…We then performed a meta‐analysis using 6 RCTs. 631 , 632 , 633 , 634 , 635 , 636 The estimated values of the desirable anticipated effects were as follows: mortality yielded a RD of 4 fewer per 1,000 (95%CI: 51 fewer to 62 more) (5 RCTs, n = 730), physical function evaluation yielded a MD of 0.45 higher (95%CI: 4.57 lower to 5.46 higher) (3 RCTs, n = 489), and muscle mass yielded an MD of 0.2 higher (95%CI: 0.56 lower to 0.96 higher) (2 RCTs, n = 157). It was adjudged that the desirable anticipated effects were trivial.…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%